Penambahan Tepung Ikan Lele Dan Tepung Kedelai Pada Biskuit Modified Cassava Flour Untuk Lansia - Widyaniputria, Rachmah Fathia; dahlia, Noli Novi; Nur'utami, Dwi Aryanti; Nurwitri, CC (JURNAL AGROINDUSTRI HALAL, 2020)
Elderly need adequate intake to prevent health problems. One of the intake can be obtained from snack such as biscuit. This study aims to improve nutritional quality in terms of fiber and protein by the addition of local food sources such as mocaf, catfish flour and soy flour as a source of protein. This research used catfish flour and soy flour with concentration about 11%: 6%, 14%: 3%, and 17%: 0%. Biscuit was hedonic testing by the elderly as untrained panelists, chemically consist proximate, crude fiber, total energy content and analyzed physically namely texture analysis (hardness). The results showed that the addition of 17% catfish flour and 0% soy flour was the most preferred biscuits from the parameters of color, aroma, texture, and taste. Nutrient content of were 3.69% water content, 3.12% ash content, 12.19% protein content, 29.23% fat content, 51.77% carbohydrate content, 1.37% crude fiber content, and a total energy 519 Kcal/100 grams with a hardness value of 987.00 gf (gramforce). Keywords : biscuit, mocaf, catfish flour, soybean flour